2019
DOI: 10.3390/polym11040639
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Studies on the Effect of Material Characteristics and Runners Layout Geometry on the Filling Imbalance in Geometrically Balanced Injection Molds

Abstract: Simulation studies were performed on filling imbalance in geometrically balanced injection molds. A special simulation procedure was applied to simulate properly the phenomenon, including inertia effects and 3D tetrahedron meshing as well as meshing of the nozzle. The phenomenon was investigated by simulation using several different runner systems at various thermo-rheological material parameters and process operating conditions. It has been observed that the Cross-WLF parameters, index flow, critical shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Later, the basic research in this field was performed first by Potente et al [136,137], and then by Steller et al [138,139] as well as by Covas et al [140]. Recently, Wilczyński et al [141] performed experimental studies on the melting mechanism of polymers in injection molding machines. It has been observed that melting in the injection molding machine occurs to some extent, according to the Tadmor mechanism, with clearly visible starvation (Figure 8).…”
Section: Melting Sectionmentioning
confidence: 99%
“…Later, the basic research in this field was performed first by Potente et al [136,137], and then by Steller et al [138,139] as well as by Covas et al [140]. Recently, Wilczyński et al [141] performed experimental studies on the melting mechanism of polymers in injection molding machines. It has been observed that melting in the injection molding machine occurs to some extent, according to the Tadmor mechanism, with clearly visible starvation (Figure 8).…”
Section: Melting Sectionmentioning
confidence: 99%
“…The factor of mass filling imbalance I m [2] has been applied to evaluate the degree of imbalance which is defined as…”
Section: Optimization Windowmentioning
confidence: 99%
“…However, there is not any commonly accepted procedure for problem solving. A detailed discussion of the literature review has been recently presented by the authors of this paper [1,2]. This review is summarized below.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations